Implementasi Gaya Kepemimpinan Kapolsek Untuk Meningkatkan Kinerja Anggota Polsek Karawang Kota - Riska Dewi; Sungkono S (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
This study aims to determine the role of the Kapolsek leadership style in improving the performance of members. The leadership style of the Kapolsek has a very important role in creating a conducive work environment, motivating members and achieving the desired results in law enforcement and community security. This practical work method uses the observative method. In this method is described as a method used in observing and describing the behavior of the subject. The problem is regarding this democratic leadership style, if a discussion is held for decision making, the leader cannot communicate well and cannot make decisions quickly when problems occur. In a group with many voices, of course the discussion will be hampered, so the leader must play a more active role as a mediator so that all voices can be conveyed. The location of this practical work is at the Karawang City Police, data are collected through in-depth interviews, field surveys and recording of the necessary secondary data. The results of this practical work show that an effective Kapolsek leadership style involves clear vision, effective communication, member empowerment, coaching and support as well as recognition for achievements. Implementation of such a leadership style can improve the performance of members of the police force, strengthen motivation and make a positive contribution in maintaining security and public order.